Invasion of privacy by smart meters: An analysis of consumer concerns. Issue 3 (3rd July 2017) - Huang, Ziyue; Palvia, Prashant
ABSTRACT: While smart meters offer an innovative way to solve energy problems, they have also brought concerns regarding consumer privacy. In this study, we develop an instrument to measure the consumers' concerns for information privacy (CFIP) in adopting smart meters, and propose a conceptual model to examine the relationship between privacy concerns, trusting beliefs, risk beliefs, and intention to adopt smart meters. Using both focus group study and survey methods, we show that CFIP can be measured by three dimensions: collection, secondary use, and improper access, and that the effect of CFIP on behavioral intention is fully mediated by risk beliefs.